Pharmacokinetics of Intravenous Peramivir in the Airway Epithelial Lining Fluid of Healthy Volunteers. Issue 7 (October 2016) - Funatsu, Yohei; Tasaka, Sadatomo; Asami, Takahiro; Namkoong, Ho; Fujiwara, Hiroshi; Iketani, Osamu; Yagi, Kazuma; Kimizuka, Yoshifumi; Ishii, Makoto; Nishimura, Tomoyasu; Ogata, Haruhiko; Iwata, Satoshi; et al.
Background: Some subtypes of influenza virus, such as H5N1 and H7N9, cause severe viral pneumonia, for which the intraluminal concentration of the anti-influenza agent in the airway is critical. However, the pharmacokinetics of peramivir, the only available injectable neuraminidase inhibitor formulation, in the airway epithelial lining fluid (ELF) remains unclear. In this study, we aimed to determine the time course of peramivir in the pharyngeal ELF, bronchial ELF and plasma of healthy volunteers using bronchoscopic microsampling technique. Methods: Six healthy volunteers were studied. After baseline plasma sampling, 0.3 g peramivir was intravenously injected over 0.5 h. ELF was obtained from the upper and lower airways using bronchoscopic microsampling at the end of the infusion (0.5 h) and after 1.0, 1.5, 2.0, 2.5, 3.0, 4.0 and 5.0 h. The concentrations of peramivir in the ELFs and in the plasma were quantified by LC/MS/MS analysis. Results: The mean maximum concentration (Cmax ) in pharyngeal ELF, bronchial ELF and plasma was 1.20 ±0.42, 9.60 ±2.30 and 50.52 ±17.51 ng/ml, respectively. The penetration ratio at Cmax in pharyngeal and bronchial ELFs was 2.4 and 19.0, respectively. The ratio of the area under the curve from 0 to infinity in pharyngeal and bronchial ELFs was 4.8 and 39.1 mgmin/l, respectively. Conclusions: The time course of peramivir concentration in the ELFs revealed that concentrations above the 50% inhibitory concentration value of influenza were achieved in the upper and lower airways. Therefore, peramivir could be an important treatment option for influenza viral pneumonia.